1996
DOI: 10.1046/j.1365-2133.1996.122857.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple basal cell carcinomas: no association withHLA-DRB, HLA-DQAIorHLA-DQBIin Swedish patients

Abstract: Many diseases with autoimmune features are associated with alleles of the human leucocyte antigen (HLA). However, few if any malignant disorders have reproducibly been shown to be HLA-associated. In three independent studies, using serological tissue typing techniques, an increase of the HLA class II specificity DR1 has been found in patients with multiple basal cell carcinomas. These observations prompted us to determine the frequencies of DRB1, DQA1, and DQB1 alleles by high-resolution genomic tissue-typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…11 We cannot exclude, however, the possibility that an association between these alleles and skin cancer still exists but could not be detected in our study because of the small size of the study population.…”
Section: Commentmentioning
confidence: 42%
See 1 more Smart Citation
“…11 We cannot exclude, however, the possibility that an association between these alleles and skin cancer still exists but could not be detected in our study because of the small size of the study population.…”
Section: Commentmentioning
confidence: 42%
“…[9][10][11][12][13][14][15][16][17] In the immunocompetent population, the most consistent reported association is of the HLA-DR1 allele with (usually multiple) basal cell carcinoma 12,15,18,19 and a negative association of basal cell carcinoma with the HLA-DR4 allele, 10,12,18 although these associations could not always be confirmed. 11 Several studies of renal transplant recipients reported a positive association between the HLA-DR7 allele and squamous cell carcinomas or basal cell carcinomas. 16,20 Because of the small sample size in this study of inhabitants on the tropical island of Saba, we limited our study to the association of basal cell carcinoma and squamous cell carcinoma with the HLA alleles, which have previously been reported to be associated with one of these skin cancers (ie, HLA-DR1, HLA-DR4, and HLA-DR7).…”
mentioning
confidence: 89%
“…20 Emtestam et al found no association between class II (DR) antigens and the risk of multiple BCC in Swedish patients and concluded that genetic factors associated with the class II region do not contribute significantly to the aetiology of multiple BCC. 37 Fifteen studies have examined Celtic ancestry as a risk factor for skin cancer. 1 Six of these studies demonstrated an increased risk of NMSC, three an increased risk of MM and two studies found an increased risk of both MM and NMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of HLA alleles with NMSC have been described both in renal transplant recipients and non‐immunosuppressed patients (12–18). In the immunocompetent population, BCC has been associated positively with the HLA‐DR1 or DR7 alleles (12–15, 19) and negatively with the HLA‐DR4 allele (19, 20), but not consistently (21). The HLA‐A11 or B27 alleles have also been associated with NMSC (12, 18).…”
mentioning
confidence: 99%